Does Formulation of Service Users' Difficulties Improve Empathy in Forensic Mental Health Services?. Issue 3 (27th May 2017) - Wilkinson, Helen; Whittington, Richard; Perry, Lorraine; Eames, Catrin
ABSTRACT: The culture and values of the National Health Service and the staff that work within it have received much attention over recent years. The erosion of empathy and compassionate care toward service users has been highlighted. Psychological formulation may be one way that clinicians can understand their service users more fully, which could lead to an improvement in the empathy they express toward them. The current study investigates the effect of presenting client information in a psychological formulation on self-reported empathy in staff in medium and low secure forensic mental health services. One hundred and fifty-four staff were recruited via convenience sampling to complete self-report questionnaires measuring burnout (Maslach Burnout Inventory), state (Adapted Interpersonal Reactivity Index), and trait (Empathy Quotient) empathy. No significant difference in state empathy scores was observed among the staff in the formulated group when compared with the unformulated group. Linear multiple stepwise regressions demonstrated that trait empathy and burnout significantly predicted variance in state empathy, but the information format was not significant. It was concluded that mode of presentation in this instance did not influence the degree of empathic concern staff expressed toward a hypothetical client in a vignette. General levels of empathy and degree of burnout superseded this effect. Further research is needed on how adjusting client information formats might enhance empathy among professionals.